Komunikasi Antar Pribadi Jarak Jauh Antara Anak Dengan Orang Tua - Hsb, Fadhil M; S, Aisyah; A, Yaldi; Hsb R, Rahmat Hidayat (Yayasan Daarul Huda Kruengmane, 2024)
Long distance interpersonal communication between children and parents has become an important discussion in the current modern era. This article examines changes in communication and the impact of technology and strategies for maintaining strong relationships despite being separated in different locations. This article aims to understand how this communication technique works, especially among students who live far from their parents. This article reveals that there are various kinds of families with different communication patterns, including technologically challenged career families and broken homes. Barriers such as economic factors, professional time and communication networks often influence the effectiveness of communication. The results of this article show that established communication patterns can strengthen or weaken the emotional relationship between children and parents. depends on how effectively they communicate despite being separated by distance and this article provides insight into the importance of long-distance interpersonal communication and its impact on family relationship dynamics. It is hoped that these results can be a guide for families experiencing similar situations to improve the quality of their communication